Socialization of Halal Certification to Develop MSEs: Case Study in Jabung, Malang Regency - Munawar Ismail; Yenny Kornitasari (Universitas Brawijaya, 2022)
Micro and Small Enterprises (MSEs) have an important role to increase economic growth. So, one of the efforts to improve the quality of MSEs is halal certification. Indonesia as a country with the moeslem majority, halal issue is crucial especially for products. With the halal certification, MSEs in Indonesia have competitive advantages in the international markets. Therefore, the community empowerment program aims to increase sales of MSEs products with the socialization activities and technical guide about the halal certification in Jabung District. There are several steps to do community empowerment, (i) identification through distributing questionnaires, (ii) socialization and guide the participants with the discussion and evaluation methods. The result in this identification found that most of the MSE sell food and beverages, but most of them did not have a halal certification on the products. Thus, the awareness of the MSEs about the halal certification increases because of the community empowerment program. This result can be seen from the management process in MSEs.